Polyphenolics and Chemical Profiles of Domestic Norwegian Apple (Malus × domestica Borkh.) Cultivars - Fotirić Akšić, Milica; Nešović, Milica; Ćirić, Ivanka; Tešić, Živoslav; Pezo, Lato; Tosti, Tomislav; Gašić, Uroš; Dojčinović, Biljana; Lončar, Biljana; Meland, Mekjell (Frontiers in Nutrition, 2022)
Using modern analytical techniques, a comprehensive study of the chemical composition of fruits from apple cultivars grown in western Norway during 2019 and 2020 were done. Metals, sugars, organic acids, antioxidant tests, and polyphenol content have been observed. In all investigated samples the most dominant sugars were glucose, fructose, and sucrose. Among eleven tested organic acids, the dominant was malic acid, followed by citric and maleic acid. The most common metal was potassium, followed by magnesium and zinc. The quantification of polyphenols showed that among the eleven quantified polyphenols, chlorogenic acid, quercetin 3-O-rhamnoside, quercetin 3-O-glucoside, quercetin, and phlorizin were the most abundant. A detailed study of the polyphenolic profile of nine investigated apple samples provided 30 identified polyphenolic compounds from the class of hydroxybenzoic and hydroxycinnamic acids, flavonoids, and dihydrochalcones. In addition to the identified 3-O-caffeoylquinic acid, its two isomers of 5-O-caffeoylquinic acid and three esters were also found. Present polyphenols of the tested apples provided a great deal of data regarding their quality but are also a good marker to distinguish growing locations.